Enhanced Tolerance to Methyl Viologen-Mediated Oxidative Stress via AtGR2 Expression From Chloroplast Genome - Wang, Bipeng; Ding, HaiYan; Chen, Qiqi; Ouyang, Li; Li, Shengchun; Zhang, Jiang (Frontiers in Plant Science, 2019)
Owing to their sessile life habit, plants are continuously subjected to a broad range of environmental stresses. During periods of (a)biotic stresses, reactive oxygen species (ROS) levels can rise excessively, leading to oxidative stress. Glutathione reductase (GR) plays an important role in scavenging the ROS and maintenance of redox potential of the cell during oxidative stress. To enhance ROS scavenging capacity, and hence stress tolerance, the Arabidopsis thaliana GR2 (AtGR2) gene was expressed from the tobacco plastid (chloroplast) genome, the main source of ROS production in plant photosynthetic tissues, in this study. Leaves of transplastomic tobacco plants had about 7 times GR activity and 1.5 times total glutathione levels compared to wild type. These transplastomic tobacco plants showed no discernible phenotype and exhibited more tolerance to methyl viologen (MV) induced oxidative stress than wild-type control plants. The results indicate that introducing AtGR2 in chloroplasts is an efficient approach to increase stress tolerance. This study also provides evidence that increasing antioxidant enzyme via plastid genome engineering is an alternative to enhance plant’s tolerance to stressful conditions.